Aggravated solitary confinement in Turkey. A form of institutionalised torture - Martín , Paula; Guelbenzu, Altamira (Torture Journal, 2024)
Last January 2023 we were part of the International Delegation Against Isolation that travelled to Turkey to hold meetings with civil society organisations and political circles regarding the prison situation. The visit was followed by a report prepared by the Delegation: "Solitary Confinement and Isolation Policies in Turkey", released in March 2023. This text reflects some of the visit's conclusions and the subsequent monitoring of the current situation of human rights and prisons in Turkey concerning aggravated solitary confinement.